Respuesta :
Answer:
-1
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
−4(y−2)=12
(−4)(y)+(−4)(−2)=12(Distribute)
−4y+8=12
Step 2: Subtract 8 from both sides.
−4y+8−8=12−8
−4y=4
Step 3: Divide both sides by -4.
−4y
−4
=
4
−4
y=−1
Answer:
Step-by-step explanation:
Here you go mate
PEMDAS
Parenthesis
Exponent
Multiplication
Division
Addition
Subtraction
Step 1
-4(y-2)=12 Remove parenthesis
-4y+8=12
Step 2
-4y+8=12 Subtract -8
-4y=4
Step 3
-4y=4 Divide both sides by 4
-4/4+4/4
answer
y=-1